4-Cyano-5-(2-thiophenyl)-pyrazoles are high affinity CB1 receptor ligands1. Issue 18 (5th March 2015) - Altomonte, Stefano; Baillie, Gemma L.; Ross, Ruth A.; Zanda, Matteo
<x xml:space="preserve">Abstract</x> Introduction of a 4-CN group on 5-thiophenyl-pyrazoles afforded high affinity cannabinoid ligands having low nM Ki values and moderate CB1 receptor selectivity. Log P and TPSA values suggest that some of the compounds might be peripherally restricted.